Remote Subthreshold Stimulation Enhances Skin Sensitivity in the Lower Extremity - Plater, Emma B.; Seto, Vivian S.; Peters, Ryan M.; Bent, Leah R. (Frontiers in Human Neuroscience, 2021)
Foot sole skin interfaces with the ground and contributes to successful balance. In situations with reduced sensitivity in the glabrous foot skin, stochastic resonance (SR) improves skin sensitivity by adding tactile noise. Some situations, however, involve an interface comprised of hairy skin, which has higher thresholds for sensitivity. For example, in lower extremity amputation the residual limb is comprised of hairy leg skin. The main objective of this study was to determine if SR improves skin sensitivity in hairy skin, and whether a specific intensity of noise is most effective. Secondary objectives were to compare the effect between locations, ages and modalities. In 60 healthy participants a vibrotactile (test) input was delivered at the lower extremity concurrently with a second, noisy stimulus applied more proximally. The presence of a remote SR effect was tested in 15 young participants using electrotactile noise at the calf. Secondary objectives were tested in separate groups of 15 subjects and differed by substituting for one of the three variables: vibrotactile noise, heel site, and with older participants. A forced-choice protocol was used to determine detection ability of the subthreshold vibration test input with varying noise levels applied simultaneously (0, 20, 40, 60, 80, 100% of perceptual threshold). An SR effect was identified when increased detection of the input was obtained at any level of noise versus no noise. It was found that all four test groups demonstrated evidence of SR: 33-47% of individuals showed better detection of the input with added noise. The SR effect did not appear consistently at any specific noise level for any of the groups, and none of the variables showed a superior ability to evoke SR. Interestingly, in approximately 33% of cases, threshold values fluctuated throughout testing. While this work has provided evidence that SR can enhance the perception of a vibrotactile input in hairy skin, these data suggest that the ability to repeatably show an SR effect relies on maintaining a consistent threshold.